STRATEGI IMPLEMENTASI KEBIJAKAN HUTAN TANAMAN RAKYAT DI KABUPATEN SAROLANGUN, JAMBI - Dewi Febriani; Dudung Darusman; Dodik Ridho Nurrochmat; Nurheni Wijayanto (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2012)
Commmunity Plantation Forest is Indonesian government policy which needed participation and responsibility from local community to manage production forest sustainability. Studies on capacity of community as prominent agent are needed. The objectives of this study are: (1) to assess the physical capital, human capital and social capital of communities and to identify their participation in HTR program; (2) to analyze the correlation between physical capital and human capital with elements of social capital, and between social capital with their participation in HTR; and (3) to develop implementation strategy of HTR. Analysis of data used descriptive method, Spearman rank correlation, SWOT and QSPM. Necessary information for this study came from a survey of 81 households from Taman Bandung, Seko Besar and Lamban Sigatal villages in Sarolangun Regency, Jambi. The results showed that physical capital, human capital and social capital are included in medium category. No correlation between physical capital and social capital, but there are correlation between social capital and human capital and participation. The study also showed that selected strategy in HTR implementation are: (1) accommodate exiting community models in forest land as community motivation; (2) optimize local government support to accelerate license process, assistance, and intensive socialization about HTR; and (3) use timber scarcity issues and PT Samhutani as market opportunity issues to stimulating community to plant timber.